The key success factors in focus group discussions with the elderly for novice researchers: a review - Kasorn Muijeen; Puangpaka Kongvattananon; Chomchuen Somprasert (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - This study aimed to discuss the key success factors in focus group discussions among the elderly as a means of supporting novice researchers and also to share the experiences of novice researchers with focus group discussions. Design/methodology/approach - This study used a literature review of previous studies that revealed three themes regarding the key success of focus group discussions with the elderly. Focusing on issues published between 2009 and 2019, four health-related databases, namely the Cumulative Index of Nursing and Allied Health Literature (CINAHL), ScienceDirect, PsycARTICLES and Thaijo were investigated using keyword searches, both individually and in combination, and the inclusion criteria used in selecting relevant articles as primary sources included research written in the English and Thai languages. Findings - The literature review involved eight published articles related to this topic in the nursing field. Three themes for key successes were identified as follows: good planning and convenient organization, being accepting and flexible concerning their opinions and good management. Originality/value - Focus group discussions with the elderly are complex and challenging for novice researchers. It is necessary that a novice researcher in the nursing field builds up the skills of a moderator in conducting focus group interviews if he or she wishes to obtain rigorous data.